2013
DOI: 10.1128/jvi.00865-13
|View full text |Cite
|
Sign up to set email alerts
|

Early Gag Immunodominance of the HIV-Specific T-Cell Response during Acute/Early Infection Is Associated with Higher CD8 + T-Cell Antiviral Activity and Correlates with Preservation of the CD4 + T-Cell Compartment

Abstract: The important role of the CD8؉ T-cell response on HIV control is well established. Moreover, the acute phase of infection represents a proper scenario to delineate the antiviral cellular functions that best correlate with control. Here, multiple functional aspects (specificity, ex vivo viral inhibitory activity [VIA] and polyfunctionality) of the HIV-specific CD8 ؉ T-cell subset arising early after infection, and their association with disease progression markers, were examined. Blood samples from 44 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 63 publications
5
64
0
Order By: Relevance
“…Our findings accord with recent data (17) showing that viral control of HIV-2 was significantly associated with a high-magnitude, polyfunctional Gag-specific CD8 ϩ T cell response. This further confirms the prevailing notion that immune responses to Gag possess enhanced antiviral potency compared to other specificities, likely as a result of its conservation and the higher rate of viral escape that exacts a fitness cost for HIV (18)(19)(20). More intriguing is the association we found with Nefspecific responses and lower VSP.…”
supporting
confidence: 78%
“…Our findings accord with recent data (17) showing that viral control of HIV-2 was significantly associated with a high-magnitude, polyfunctional Gag-specific CD8 ϩ T cell response. This further confirms the prevailing notion that immune responses to Gag possess enhanced antiviral potency compared to other specificities, likely as a result of its conservation and the higher rate of viral escape that exacts a fitness cost for HIV (18)(19)(20). More intriguing is the association we found with Nefspecific responses and lower VSP.…”
supporting
confidence: 78%
“…Our finding that Nef-specific CTLs have no effect on the viremia set point after acute infection is similar to recent data from Turk et al (38), but it contradicts another recent study by Riou et al, in which a correlation between polyfunctional Nef-specific CTLs and a lower viremia set point was observed (21). Similarly, there are contradictory results from recent SIV-macaque vaccine studies, some of which showed an important contribution of Nef-specific CTLs to the control of viremia (22) while others showed that Nef-specific CTLs failed to control viremia and are easily escaped from in acute infection (23,24).…”
Section: Discussionsupporting
confidence: 82%
“…We previously demonstrated that Gag-and Nefdominant soluble activity mediated by CD8 ϩ T cells during acute HIV-1 infection corresponded to the breadth of virus inhibition, as well as immune pressure against transmitted founder viruses, but that this activity was diminished by 6 months postinfection in the patients examined (6). Others have also reported early Gag and Nef CD8 ϩ T cell antiviral activity in acute infection (68,69). In addition, MIP-1␤, which correlated with inhibition in this study, correlated with initial CD8 ϩ T cell antiviral responses in acute HIV-1 infection (6) and initial viremic control (5).…”
Section: Discussionmentioning
confidence: 99%